Brachial Flow-Mediated Dilation and Incident Atrial Fibrillation The Multi-Ethnic Study of Atherosclerosis - O'Neal, Wesley T.; Efird, Jimmy T.; Yeboah, Joseph; Nazarian, Saman; Alonso, Alvaro; Heckbert, Susan R; Soliman, Elsayed Z. (My University, 2014)
Objective—It is unknown whether endothelial dysfunction precedes atrial fibrillation (AF) development. The objective of this study was to examine the association of brachial flow-mediated dilation (FMD) with incident AF. Approach and Results—A total of 2936 participants (mean age, 61±9.9 years; 50% women; 66% nonwhites) from the Multi-Ethnic Study of Atherosclerosis with available ultrasound brachial FMD measurements who were free of baseline AF were included in this analysis. Baseline (2000–2002) FMD was computed from the percentage difference (%FMD) in brachial artery diameter and maximum diameter during measured vasodilator response. AF was ascertained from hospitalization data including Medicare claims during a median follow-up of 8.5 years. Probability-weighted Cox proportional-hazards regression was used to compute hazard ratios and 95% confidence intervals for the association between FMD as a continuous variable (%FMD values per 1-SD increase) and incident AF. Incident AF was detected in 137 (4.7%) participants. Those with %FMD values below the sex-specific median value (median %FMD; men, 3.6%; women, 4.2%; incidence rate per 1000 person-years, 7.3; 95% confidence interval, 5.9–9.0) were more likely to develop AF than people whose %FMD values were above the median value (incidence rate per 1000 person-years, 4.5; 95% confidence interval, 3.4–5.8; log-rank P=0.0043). In a multivariable Cox regression analysis, each 1-SD increase in %FMD values (SD, 2.8%) was associated with less incident AF (hazard ratio, 0.84; 95% confidence interval, 0.70–0.99). These results were consistent across subgroups stratified by age, sex, and race/ethnicity. Conclusions—Smaller brachial FMD values are associated with higher rates of AF, sugges
Keywords: atrial fibrillation endothelium epidemiology